PENGARUH PENAMBAHAN TEPUNG KACANG MERAH (Phaseolus vulgaris L.) DAN KACANG METE (Anacardium ocicidentale L.) TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK COOKIES BERBASIS SAGU (Metroxylon sp). - Ainun, Poppy; Karimuna, La; Ansharullah, Ansharullah (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2020)
ABSTRACTThe purpose of this research was to study the effects of adding red bean flour and cashew nuts to the chemical characteristics and organoleptics of sago-based cookies that the panelists liked. This study used a completely randomized design (CRD) with the addition of red bean flour and cashew nuts K0 (100% control), K1 (15%: 35%), K2 (20%: 30%), K3 (25%: 25%). ), and K4 (30%: 20%). Data were analyzed using Analysis of Variances (ANOVA). The results showed that the treatment of addition of red bean flour and cashew nuts to sago-based cookies had a very significant effect on the organoleptic of aroma, taste, and texture while not significantly affecting the color of cookies. Treatment of K0 (control 100%), K1 (15%: 35%), K2 (20%: 30%), K3 (25%: 25%), and K4 (30%: 20%).%). Based on the organoleptic assessment of sago-based cookies which include color, aroma, taste and texture, the values for color were 3.56 (likes), aroma 3.87 (likes), flavor 3.70 (likes), texture 2.74 (rather like) and Proximate analysis includes water, ash, protein, fat, carbohydrate and crude fiber content with values of 8.49%, 2.26%, 6.07%, 22.13%, 61.03%, 40.34%. Based on the information obtained, the sago-based cookies product has not fulfilled INS but based on organoleptic assessment, it is acceptable (like) by panelists.Keywords : Cookies, sago, red bean flour, cashews.ABSTRAKThe purpose of this study was to study the effect of addition of red bean flour and cashews to the chemical and organoleptic characteristics of sago-based cookies which panelists liked. This study used a completely randomized design (CRD) with the addition of red bean flour and cashews, namely K0 (100% control), K1 (15%: 35%), K2 (20%: 30%), K3 (25%: 25). %), and K4 (30%: 20%). Data were analyzed using Analysis of Variance (ANOVA). The results showed that the addition of red bean flour and cashews to sago-based cookies had a very significant effect on the organoleptic assessment of aroma, taste and texture, while it had no significant effect on the organoleptic assessment of the color of cookies. Organoleptic values of sago-based cookies have organoleptic values of color, aroma, taste and texture of 3.56 (like), 3.87 (like), 3.70 (like), 2.74 (slightly like), respectively. The content of water, ash, protein, fat, carbohydrate and crude fiber were 8.49%, 2.26%, 6.07%, 22.13%, 61.03%, 40.34%, respectively.Kata kunci: cookies, sagu, tepung kacang merah, kacang mete